Long-term Implications of Persistent Diverticulitis: A Retrospective Cohort Study of 915 Patients. Issue 9 (September 2021) - Alnaki, Ali; Garfinkle, Richard; Almalki, Turki; Pelsser, Vincent; Bonaffini, Pietro; Reinhold, Caroline; Morin, Nancy; Vasilevsky, Carol-Ann; Liberman, A. Sender; Boutros, Marylise
Abstract : BACKGROUND: Persistent (or ongoing) diverticulitis is a well-recognized outcome after treatment for acute sigmoid diverticulitis; however, its definition, incidence, and risk factors, as well as its long-term implications, remain poorly described. OBJECTIVE: The purpose of this study was to assess the incidence, risk factors, and long-term outcomes of persistent diverticulitis. DESIGN: This was a retrospective cohort study. SETTINGS: Two university-affiliated hospitals in Montreal, Quebec, Canada were included. PATIENTS: The study was composed of consecutive patients managed nonoperatively for acute sigmoid diverticulitis. INTERVENTION: Nonoperative management of acute sigmoid diverticulitis was involved. MAIN OUTCOME MEASURES: Persistent diverticulitis, defined as inpatient or outpatient treatment for signs and symptoms of ongoing diverticulitis within the first 60 days after treatment of the index episode, was measured. RESULTS: In total, 915 patients were discharged after an index episode of diverticulitis managed nonoperatively. Seventy-five patients (8.2%; 95% CI, 6.5%–10.2%) presented within 60 days with persistent diverticulitis. Factors associated with persistent diverticulitis were younger age (adjusted OR = 0.98 (95% CI, 0.96–0.99)), immunosuppression (adjusted OR = 2.02 (95% CI, 1.04–3.88)), and abscess (adjusted OR = 2.05 (95% CI, 1.03–3.92)). Among the 75 patients with persistent disease, 42 (56.0%) required hospital admission, 6 (8.0%) required percutaneous drainage, and 5 (6.7%) required resection. After a median follow-up of 39.0 months (range, 17.0–67.3 mo), the overall recurrence rate in the entire cohort was 31.3% (286/910). After excluding patients who were managed operatively for their persistent episode of diverticulitis, the cumulative incidence of recurrent diverticulitis (log-rank: p < 0.001) and sigmoid colectomy (log-rank: p < 0.001) were higher among patients who experienced persistent diverticulitis after the index episode. After adjustment for relevant patient and disease factors, persistent diverticulitis was associated with higher hazards of recurrence (adjusted HR = 1.94 (95% CI, 1.37–2.76) and colectomy (adjusted HR = 5.11 (95% CI, 2.96–8.83)). LIMITATIONS: The study was limited by its observational study design and modest sample size. CONCLUSIONS: Approximately 10% of patients experience persistent diverticulitis after treatment for an index episode of diverticulitis. Persistent diverticulitis is a poor prognostic factor for long-term outcomes, including recurrent diverticulitis and colectomy. See Video Abstract at http://links.lww.com/DCR/B593 . REPERCUSIONES A LARGO PLAZO DE LA DIVERTICULITIS PERSISTENTE: ESTUDIO DE UNA COHORTE RETROSPECTIVA DE 915 PACIENTES: ANTECEDENTES: La diverticulitis persistente (o continua) es un resultado bien conocido posterior al tratamiento de la diverticulitis aguda del sigmoides; sin embargo, la definición, incidencia y factores de riesgo, así como sus repercusiones a largo plazo siguen estando descritas de manera deficiente. OBJETIVO: Evaluar la incidencia, los factores de riesgo y los resultados a largo plazo de la diverticulitis persistente. DISEÑO: Estudio de una cohorte retrospectiva. AMBITO: Dos hospitales universitarios afiliados en Montreal, Quebec, Canadá. PACIENTES: pacientes consecutivos tratados sin cirugia por diverticulitis aguda del sigmoides. INTERVENCIÓN: Tratamiento no quirúrgico de la diverticulitis aguda del sigmoides. PRINCIPALES RESULTADOS EVALUADOS: Diverticulitis persistente, definida como tratamiento hospitalario o ambulatorio por signos y síntomas de diverticulitis continua dentro de los primeros 60 días posteriores al tratamiento del episodio índice. RESULTADOS: Un total de 915 pacientes fueron dados de alta posterior al episodio índice de diverticulitis tratados sin cirugia. Setenta y cinco pacientes (8, 2%; IC del 95%: 6, 5-10, 2%) presentaron diverticulitis persistente dentro de los 60 días. Los factores asociados con la diverticulitis persistente fueron una edad menor (aOR: 0, 98, IC del 95%: 0, 96-0, 99), inmunosupresión (aOR: 2, 02, IC del 95%: 1, 04-3, 88) y abscesos (aOR: 2, 05, IC del 95%: 1, 03-3, 92). Entre los 75 pacientes con enfermedad persistente, 42 (56, 0%) requirieron ingreso hospitalario, 6 (8, 0%) drenaje percutáneo y 5 (6, 7%) resección. Posterior a seguimiento medio de 39, 0 (17, 0-67, 3) meses, la tasa global de recurrencia de toda la cohorte fue del 31, 3% (286/910). Después de excluir a los pacientes que fueron tratados quirúrgicamente por su episodio persistente de diverticulitis, la incidencia acumulada de diverticulitis recurrente (rango logarítmico: p <0, 001) y colectomía sigmoidea (rango logarítmico: p <0, 001) fue mayor entre los pacientes que experimentaron diverticulitis persistente después el episodio índice. Posterior al ajuste de factores importantes de la enfermedad y del paciente, la diverticulitis persistente se asoció con mayores riesgos de recurrencia (aHR: 1, 94, IC 95% 1, 37-2, 76) y colectomía (aHR: 5, 11, IC 95% 2, 96-8, 83). LIMITACIONES: Diseño de estudio observacional, un modesto tamaño de muestra. CONCLUSIONES: Aproximadamente el 10% de los pacientes presentan diverticulitis persistente después del tratamiento del episodio índice de diverticulitis. La diverticulitis persistente, en sus resultados a largo plazo, es un factor de mal pronóstico, donse se inlcuye la diverticulitis recurente y colectomía. Consulte Video Resumen en http://links.lww.com/DCR/B593 .